2022
DOI: 10.7759/cureus.21127
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease-Associated Pruritus: A Glance at Novel and Lesser-Known Treatments

Abstract: Chronic kidney disease-associated pruritus (CKD-aP), also known as uremic pruritus, has been associated with increased mortality and lower quality of life among patients with chronic kidney disease (CKD). The relentless nature of the condition is mainly due to its diverse and complex etiologies, which are still being studied. Despite the introduction of many agents to treat it, the resolution rates of CKD-aP still remain unsatisfactory. This study sought to review the lesser-known/novel treatments and establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Accumulation of P, Ca, Al, and Mg can contribute to pruritus [ 37 , 38 , 39 ]. Hypercalcemia and hyperphosphatemia were identified as independent risk factors for CKD-associated pruritus [ 9 ].…”
Section: Pathogenesis Of Ckd-associated Pruritusmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of P, Ca, Al, and Mg can contribute to pruritus [ 37 , 38 , 39 ]. Hypercalcemia and hyperphosphatemia were identified as independent risk factors for CKD-associated pruritus [ 9 ].…”
Section: Pathogenesis Of Ckd-associated Pruritusmentioning
confidence: 99%
“…Unfortunately, treatment guidelines for CKD-associated pruritus have not yet been established. Treatment methods such as emollients, antihistamines, topical steroids, and ultraviolet therapy are a few of the agents currently being used [ 37 ]. These treatments are generally helpful in treating itching from various causes and can be tried first because as they do not have serious side effects.…”
Section: Treatment Of Ckd-associated Pruritusmentioning
confidence: 99%
“…Although the definite mechanisms for uremic CKD-aP have not been determined, some pathologic mechanisms are proposed for uremic CKD-aP such as increasing oxidants and inflammatory processes, loss of serum anti-oxidants in CKD patients during HD, imbalance of ions and electrolytes, and inability to excrete nitrogen products and other waste materials ( 11 ). Recent studies suggested using anti-inflammatory and antioxidant agents could lead to reduce pruritus ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antihistamines, gabapentin, and opioid-receptor modulators are the current treatments for UP, but these show variable therapeutic responses and potential side effects in patients with CKD (4,6). Many adjuvant therapies including phototherapy, acupuncture, diet supplement, and sodium thiosulphate injection have recently been reported (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%